2009
DOI: 10.5194/angeo-27-4197-2009
|View full text |Cite
|
Sign up to set email alerts
|

Inferring hydroxyl layer peak heights from ground-based measurements of OH(6-2) band integrated emission rate at Longyearbyen (78° N, 16° E)

Abstract: Abstract. Measurements of hydroxyl nightglow emissions over Longyearbyen (78 • N, 16 • E) recorded simultaneously by the SABER instrument onboard the TIMED satellite and a ground-based Ebert-Fastie spectrometer have been used to derive an empirical formula for the height of the OH layer as a function of the integrated emission rate (IER). Altitude profiles of the OH volume emission rate (VER) derived from SABER observations over a period of more than six years provided a relation between the height of the OH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 36 publications
3
47
0
Order By: Relevance
“…The peak height decreases with increasing latitude. Qualitatively similar results were presented by Liu and Shepherd (2006) for data collected by WINDII on 29 August 1992, who showed an anticorrelation between the layer altitude and the integrated emission rates of the OH * emission profiles for the latitudinal band between 32.5 and 37.5 • N. Also, Mulligan et al (2009) found an inverse behavior between layer height and OH * intensity in high latitude (78 • N) inferred from SABER measurements on the TIMED satellite. For an essentially larger time and latitudinal interval, von Savigny (2015) Grygalashvyly et al (2014): the concentration of OH * is directly proportional to pressure and, consequently, inversely proportional to altitude.…”
Section: Correlations and Intra-annual Variabilitysupporting
confidence: 71%
See 1 more Smart Citation
“…The peak height decreases with increasing latitude. Qualitatively similar results were presented by Liu and Shepherd (2006) for data collected by WINDII on 29 August 1992, who showed an anticorrelation between the layer altitude and the integrated emission rates of the OH * emission profiles for the latitudinal band between 32.5 and 37.5 • N. Also, Mulligan et al (2009) found an inverse behavior between layer height and OH * intensity in high latitude (78 • N) inferred from SABER measurements on the TIMED satellite. For an essentially larger time and latitudinal interval, von Savigny (2015) Grygalashvyly et al (2014): the concentration of OH * is directly proportional to pressure and, consequently, inversely proportional to altitude.…”
Section: Correlations and Intra-annual Variabilitysupporting
confidence: 71%
“…1995a, 1995b, 1997), Yee et al (1997), She and Lowe (1998), Reisin (2000, 2010), Bittner et al (2000Bittner et al ( , 2002, Yamada et al (2001), Liu and Shepherd (2006), Reisin and Scheer (2004), Espy et al (2007, Mulligan et al (2009), Xu et al (2010, and von Savigny et al (2012Savigny et al ( , 2015. In an earlier paper, Yee et al (1997) stated that the quantitative comparison between theoretical and experimental brightness is rather poor.…”
Section: G R Sonnemann Et Al: Hydroxyl Layer 751mentioning
confidence: 99%
“…Then, they subdivided latitudinal band into five bins and derived coefficients for each one. In a later study, the coefficients for the given empirical formula were derived for 78 ± 5 • N (Mulligan et al, 2009). This is evident from analytical Eq.…”
Section: Discussionmentioning
confidence: 99%
“…This subject was empirically investigated in a number of works (Yee et al, 1997;Liu and Shepherd, 2006;Mulligan et al, 2009). Liu and Shepherd (2006), based on WINDII measurements for the latitude band 40 • S-40 • N and the period from November 1991 to August 1997, derived an empirical formula for the dependence of the height of the layer on integrated intensity (that is equivalent to number density), day of year, and local time.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is to use observations with more than one instrument and determine whether to triangulate OH observations at separated locations (Kubota et al, 1999;Ejiri et al, 2002;Kataoka et al, 2013) or to correlate them with simultaneous ground-based wind measurements (Yu et al, 2017). Another possibility is to employ the OH intensities measured from the ground to infer the OH emission altitude, relying on the fact that the latter depends quasi-linearly on the former (Yee et al, 1997;Melo et al, 1999;Liu and Shepherd, 2006;Mulligan et al, 2009;von Savigny, 2015). In this context, Liu and Shepherd (2006) proposed a method to predict the altitude of the OH layer from ground-based instrument measurements of intensities by using an empirical function derived from space-based instrument measurements.…”
Section: Introductionmentioning
confidence: 99%